Системы управления и топливоснабжения модульного учебно-тренировочного комплекса для моделирования опасных факторов пожара - Lakhvich, Вячеслав; Gorokhovik, Михаил; Sadovskiy, Андрей; Polevoda, Иван; Kuz'mitskiy, Валерий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The control and fuel supply systems for modular training complex, which is developed in the Institute for Command Engineers of the Ministry for Emergencies of the Republic of Belarus, are characterized. The design and operation of the original burner providing the simulation of fire load in three modes are described.